FAKTOR-FAKTOR YANG MEMPENGARUHI PERILAKU IMPULSE BUYING KONSUMEN PRODUK ORIFLAME DI KOTA LANGSA - Meutia Dewi (Niagawan, 2021)
The purpose of this study was to determine the effect of personal selling, price discount, and bonus packs on the impulse buying of Oriflame consumers in Langsa City. The sample in this study amounted to 97 respondents. The sampling technique used in this study is non-probability sampling. The data analysis method used in this research is multiple linear regression analysis, t test, F test and coefficient of determination. The regression equation in this study is: Y = 4.239 + 0.300x1+ 0.124x2 + 0.339x3. The constant 4.239 shows the value of impulse buying if personal selling, price discounts and bonus packs are fixed. The coefficients of personal selling variables, price discounts and bonus packs have a positive effect on impulse buying of consumers of Oriflame products in Langsa City. Based on partial and simultaneous hypothesis testing, personal selling, price discount and bonus pack variables have a significant effect on impulse buying. The value of the coefficient of determination of 0.604 or 60.4% can be concluded that impulse buying can be explained by personal selling, price discounts, and bonus packs, while the remaining 39.6% can be explained by factors not included in the study.